2022
DOI: 10.2106/jbjs.22.00280
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Compared with General Anesthesia in Contemporary Primary Total Hip Arthroplasties

Abstract: Background: The specific advantages of spinal anesthesia compared with general anesthesia for primary total hip arthroplasty (THA) remains unknown. Therefore, this study aimed to investigate the pain control, length of stay, and postoperative outcomes associated with spinal anesthesia compared with general anesthesia in a large cohort of primary THAs from a single, high-volume academic institution.Methods: We retrospectively identified 13,730 primary THAs (11,319 patients) from 2001 to 2016 using our total joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The length of hospital stay is often used as a proxy for postoperative complications and healthcare resource utilization. Consistent with findings of several retrospective cohort studies, RA also decreases the length of hospital stay relative to GA [49,50]. Notably, shorter hospital stays mean not only fewer financial costs for patients and burden on healthcare system, but also reduced exposure of frail patients to hospital-acquired infections.…”
Section: Discussionsupporting
confidence: 85%
“…The length of hospital stay is often used as a proxy for postoperative complications and healthcare resource utilization. Consistent with findings of several retrospective cohort studies, RA also decreases the length of hospital stay relative to GA [49,50]. Notably, shorter hospital stays mean not only fewer financial costs for patients and burden on healthcare system, but also reduced exposure of frail patients to hospital-acquired infections.…”
Section: Discussionsupporting
confidence: 85%
“…We also found that general anaesthesia was an independent risk factor for postoperative hypoxaemia, which may be related to postoperative pain, opioid administration, and postoperative muscular strength. A study has shown that for hip surgery, compared with general anaesthesia, patients who received intrathecal anaesthesia had lower pain scores at all evaluated time points and required less postoperative oral morphine ( 33 ). Postoperative pain was associated with postoperative hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Owen and al, patients who received spinal anesthesia had lower mean pain scores throughout length of their hospitalizations, and required fewer blood transfusions (OR, 0.7), length of stay was not significantly different between the groups, and there was no difference in readmissions at 30 or 90 days or venous thromboembolic events at 90 days [24]. The Memtsoudis meta-analysis (94 studies) also shows a reduction in bleeding and transfusion in patients undergoing spinal anesthesia [25].…”
Section: • Transfusionmentioning
confidence: 97%